2012
DOI: 10.1186/1471-2407-12-146
|View full text |Cite
|
Sign up to set email alerts
|

HOXA1 is overexpressed in oral squamous cell carcinomas and its expression is correlated with poor prognosis

Abstract: BackgroundHOX genes encode homeodomain-containing transcription factors involved in the regulation of cellular proliferation and differentiation during embryogenesis. However, members of this family demonstrated oncogenic properties in some malignancies. The present study investigated whether genes of the HOXA cluster play a role in oral cancer.MethodsIn order to identify differentially expressed HOXA genes, duplex RT-PCR in oral samples from healthy mucosa and squamous cell carcinoma was used. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 30 publications
3
61
0
1
Order By: Relevance
“…Suggested that hypothesis based on fact that 10 to 20% of patients with oral cancer no related to use of tobacco and alcohol [11]. In literature, among oncogenic virus, Human Papilomavirus (HPV) is the most frequent in individuals with head and neck cancer [8,26,30]. In our study, no interviewed cited viruses infections as risk factor for oral cancer.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Suggested that hypothesis based on fact that 10 to 20% of patients with oral cancer no related to use of tobacco and alcohol [11]. In literature, among oncogenic virus, Human Papilomavirus (HPV) is the most frequent in individuals with head and neck cancer [8,26,30]. In our study, no interviewed cited viruses infections as risk factor for oral cancer.…”
Section: Discussionmentioning
confidence: 73%
“…Oral cancer refers to all neoplasms that occur in oral cavity and lower lip [7][8][9]. Tobacco use is a major risk factor for the development of malignant lesions in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss-of-function and lineage studies have implicated Hoxa1 in development of the inner ear, heart, neural crest specification, and hindbrain patterning (31)(32)(33). Growing evidence suggests roles for Hoxa1 in etiology of various cancers through modulation of cell proliferation, invasion, and metastasis (34)(35)(36)(37). These diverse functional roles for Hoxa1 appear to be at least partially related to its ability to influence key signaling pathways in differentiating cells (35).…”
mentioning
confidence: 99%
“…Previous studies have suggested that HOXA1 is overexpressed in various cancers, including breast, liver, oral and lung cancer (Chariot et al, 1996;Abe et al, 2006;Bitu et al, 2012;Zha et al, 2012). The forced expression of HOXA1 promoted oncogenic transformation by modulating the p44/42 MAP kinase pathway and bcl-2 in MCF-10 cells (Mohankumar et al, 2007).…”
Section: Discussionmentioning
confidence: 96%